PENGARUH PELAKSANAAN KEBIJAKAN KTSP DAN KOMPETENSI GURU (PAI) TERHADAP KINERJA PROSES BELAJAR MENGAJAR DALAM MEWUJUDKAN PERILAKU BELAJAR SISWA MADRASAH ALIYAH NEGERI KABUPATEN GARUT - Huda, Taufik (PEDAGOGIA, 2017)
This study aimed to analyze the Influence of policy implementation Unit Level Curriculum and Teacher Competence (PAI) of the Teaching and Learning Process Performance in Delivering Learning Behavior Madrasah Aliyah students Garut. The method used in this research is descriptive analysis method with survey techniques. Based on the results of testing the main hypothesis is known that Policy Implementation Unit Level Curriculum and Teacher Competence is not real and significant effect on the Performance Learning Process in Creating Student Conduct. It is seen comparison between t and t-table Based on test were obtained t-count smaller than the value t- table (t0,975; 31) is t = -0.1901 table = 2.0395. Some important discoveries related to Variable Unit Level Curriculum is Principal shall conduct an evaluation of policy implementation Unit Level Curriculum on a regular basis, to determine the progress of the implementation of curriculum policies and changes in students' behavior. While the findings are considered important in Teacher Competence variable is the complement teaching and learning, teachers utilize the facilities / infrastructure that exist such as overhead projector, internet, multimedia. In the variable performance Learning Process deemed important Teacher always put props in the learning process, so petrified students in capturing the sense that the teacher and the findings are considered important in the variable behavior of student learning is in the last three years, the percentage of students who are having problems at school because of friends / association.